Does Interest in Sex Peak at Mid-Cycle in Ovulatory Menstrual Cycles of Healthy, Community Dwelling Women? An 11-Month Prospective Observational Study. Issue 2 (3rd April 2021) - Macbeth, Allison B.; Goshtasebi, Azita; Mercer, G. William; Prior, Jerilynn C.
Abstract: Women's interest in sex is asserted to increase at the mid-cycle pre-ovulatory estradiol peak. We explored this belief in healthy, spontaneously normally menstruating/ovulating women. Women recorded "interest in sex" in a daily diary; validated Quantitative Basal Temperature analysis documented ovulation. Interest in sex showed no mid-cycle peak in 61 normal-weight, nonsmoking women, ages 33.7 ± 5.6 years, over a mean of 311 consecutive days. The cycle-plotted diary "self-worth" factor (including feelings of energy, interest in sex) also showed no mid-cycle peak. Thus, interest in sex is related more strongly to women's feelings/experiences than to hormones, challenging deterministic or sex-hormone-dependent cultural and sociobiological understandings.